Desirable Properties for 3rd Generation Cyclooxygenase-2 Inhibitors - D. Tortorella, Micky; Zhang, Yanmei; Talley, John (Mini Reviews in Medicinal Chemistry, 2016)
Coxibs are a class of powerful drugs used by millions of people worldwide to treat a wide variety of ailments such as muscular skeletal pain and inflammation. The primary mechanism of action of coxibs is the potent inhibition of the COX-2 enzyme. Unfortunately, their use is limited to patients due to a variety of factors including poor solubility, negative effects on renal clearance and increased risk of cardiovascular pathology. However, because of their effectiveness in blocking PGE2 mediated inflammation, a key pathway that drives many diseases, there is a clear unmet medical need to develop new COX-2 inhibitors that are free of the aforementioned problems. The purpose of this prospectus is to define the specific properties that are desired in 3rd generation coxibs as a starting point for the development of new and better drugs.
Keywords: COX-2